Influence of diabetes mellitus on rehabilitation with dental implants. - Castanho Zapata, Mauro; Lima Souza, Genivaldo (Brazilian Journal of Implantology and Health Sciences, 2020)
Diabetes mellitus is a chronic disease that is increasingly affecting more people around the world and is characterized by an excessive concentration of glucose in the blood. This may be due to inadequate insulin production by the pancreas (type 1 diabetes mellitus) or by the body's resistance to the action of insulin produced (type 2 diabetes mellitus). This disease has implications in the vascular system and is associated with several complications such as ischemic heart disease, nephropathies, cerebrovascular diseases, peripheral arterial disease, changes in inflammatory processes and in the immune system, among many others. Diabetic patients may also present numerous oral complications such as periodontal issues or changes in the bone repair metabolism. There are several studies with divergent conclusions regarding the influence of diabetes on oral rehabilitation with implants. This review therefore aims to focus on assessing the survival rate of implants in diabetic patients so as the impact of the disease on this rate. The studies analyzed throughout this study conclude that metabolically controlled diabetic patients can benefit from oral rehabilitation with dental implants and this is still a viable solution. Glycosylated hemoglobin is a fundamental parameter that allows us to understand if we are facing a controlled patient and within the desirable values for this type of rehabilitation. Nevertheless, there are factors to consider in these patients as delays in the healing processes and higher risk of postoperative infection that can, when not properly known and controlled, influence and interfere with the treatment. In this way, it is essential to know the entire clinical history of the patients as well as to perform laboratory tests to ensure that the necessary conditions for performing this procedure are fulfilled.